2015
DOI: 10.1093/cid/civ697
|View full text |Cite
|
Sign up to set email alerts
|

The Critical Role of the Staff Nurse in Antimicrobial Stewardship—Unrecognized, but Already There: Table 1.

Abstract: An essential participant in antimicrobial stewardship who has been unrecognized and underutilized is the "staff nurse." Although the role of staff nurses has not formally been recognized in guidelines for implementing and operating antimicrobial stewardship programs (ASPs) or defined in the medical literature, they have always performed numerous functions that are integral to successful antimicrobial stewardship. Nurses are antibiotic first responders, central communicators, coordinators of care, as well as 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
116
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(132 citation statements)
references
References 31 publications
2
116
0
7
Order By: Relevance
“…The same applies to nurse practitioners, who are an important cadre of healthcare professional with a proven track record in antibiotic prescribing in SA communities, [8] in addition to intensive-care nurses, who already play a pivotal role in multidisciplinary hospital-based stewardship programmes. [9,10] Opportunities to improve baseline knowledge of pharmacists in SA have already been identified, [2,10] and work to assess barriers and enablers to reduce variability in stewardship education at the eight SA pharmacy schools has begun.…”
Section: Guest Editorialmentioning
confidence: 99%
“…The same applies to nurse practitioners, who are an important cadre of healthcare professional with a proven track record in antibiotic prescribing in SA communities, [8] in addition to intensive-care nurses, who already play a pivotal role in multidisciplinary hospital-based stewardship programmes. [9,10] Opportunities to improve baseline knowledge of pharmacists in SA have already been identified, [2,10] and work to assess barriers and enablers to reduce variability in stewardship education at the eight SA pharmacy schools has begun.…”
Section: Guest Editorialmentioning
confidence: 99%
“…A large study including 34 hospitals in Spain demonstrated that a significant proportion of patients identified as colonized or infected with CPE during hospitalization probably acquired this organism in a nursing home during the period preceding their hospital admission. 2 In addition, a recent review of the literature demonstrated that according to US-based studies, the percentage of CPE isolates that could be associated with the community ranged from 5.6% to 10.8%. 3 We have recently demonstrated the less effective effect of fecal microbiota transplantation (FMT) on CPE compared to vancomycin-resistant Enterococci (VRE) fecal carriage.…”
Section: Iterative Fecal Microbiota Transplantations For Eradicating mentioning
confidence: 99%
“…[2,3] In this regard, effective ASPs depend largely on monitoring practices, teamwork in developing and implementing interventions, and organisational infrastructure. [2] It is therefore critical in the SA context to utilise the existing resources of pharmacists and registered nurses (RNs), who are well placed to co-ordinate anti-infective management and improve patient outcomes.…”
Section: The Current Situationmentioning
confidence: 99%
“…[3] RNs play an essential role in monitoring compliance with institutional guidelines and best practice, monitoring for drug allergies and side-effects, obtain ing and reporting of therapeutic levels, management and admini stration of medicines with mixed dosages, e.g. insulin, and ensuring timely and correct administration of antimicrobials.…”
Section: The Current Situationmentioning
confidence: 99%